MISE EN SCÈNE SINEMATOGRAFI DALAM FILM HOROR BERJUDUL PRIMBON BERTEMAKAN KEPERCAYAAN BUDAYA JAWA - Martinus Eko Prasetyo; William Sanjaya (Institut Bisnis dan Teknologi Indonesia, 2025)
Indonesian horror films initially often explore mysterious stories and ghosts from local mythology, creating a mysterious atmosphere enriched with cultural elements such as addressing themes of Javanese cultural beliefs in a film titled